HUBUNGAN ANTARA KONSUMSI MINUMAN BERPEMANIS DAN ASUPAN SERAT DENGAN KADAR GULA DARAH PADA DEWASA USIA 30-50 TAHUN DI DESA NYATNYONO KECAMATAN UNGARAN BARAT KABUPATEN SEMARANG - Hifayah; Maryanto, Sugeng; Pontang, Galeh Septiar (UNIVERSITAS NGUDI WALUYO, 2018)
Background :High blood glucose levels can be an indicator of early onset of DM. The absorption of sugar causes an increase in blood sugar levels and increase the secretion of insulin. Fiber consumption may slow gastric emptying and the absorption of blood sugar levels by the intestine. Objective :To know the correlation between sweetened drinks consumption and fiber intake with blood sugar levels in adults aged 30-50 years in the village of Nyatnyono Ungaran Regency. Method :The design of this research was descriptive correlative of cross sectional. The number of samples were 81. Intake eat measured using a food recall 3x24 hour and analyzed using nutrisurvey. Statistical analysis using Pearson Product Moment test (Î± = 0.05). Results :Low sweetened drink consumption was in 34 adults (42,0%), moderate category was in 42 adults (51,9%) high category was in 5 adults (6,2%). Less fiber intake category was in 78 adults (96,3%) good category was in 3 adults (3,7%). Good blood sugar level was in 53 adults (65.4%), moderate category was in 14 adults (17,3%), high category was in 14 adults (17,3%). There was a correlation between consumption of sweetened drink with blood sugar levels (p = 0,001, r = 0,351), there was no correlation between fiber intake with blood sugar levels (p = 0,739, r = -0,038). Conclusion :There is a correlation between sweetened drink consumption and fiber intake with blood sugar levels Abstrak : Latar Belakang: Tingginya kadar gula darah menjadi indikator awal terjadinya penyakit DM. Penyerapan gula menyebabkan peningkatan kadar gula darah dan meningkatkan sekresi insulin. Konsumsi serat dapat memperlambat pengosongan lambung dan penyerapan kadar gula darah oleh usus halus. Tujuan: Untuk mengetahui hubungan antara konsumsi minuman berpemanis dan asupan serat dengan kadar gula darah pada dewasa usia. Metode: Rancangan penelitian adalah dekriptif korelatif menggunakan pendekatan cross sectional. Jumlah sampel 81 dewasa menggunakan metode Simple Random Sampling. Asupan makan diukur menggunakan food recall 3x24 jam. Analisis statistik menggunakan uji Pearson Product Moment (Î± = 0,05). Hasil: Konsumsi minuman berpemanis terdiri dari 34 rendah (42,0%) sedang 42 (51.9%) tinggi 5 (6,2%). Asupan serat kurang 78 (96,3%) baik 3 (3,7%). Kadar gula darah baik 53 (65,4%) sedang 14 (17,3%) tinggi 14 (17,3%). Ada hubungan konsumsi minuman berpemanis dengan kadar gula darah (p=0,001, r=0,351), Tidak ada hubungan asupan serat dengan kadar gula darah (p=0,739, r= -0,038). Simpulan: Terdapat hubungan antara konsumsi minuman berpemanis dengan kadar gula darah. Tidak ada hubungan asupan serat dengan kadar gula darah.